Symptomatic Medial Bone Excrescence in the Distal Phalanx of the Hallux after the First Metatarsophalangeal Joint Arthrodesis: A Case Report and Radiographic Reviews - Yuji Maenohara; Ryutaro Takeda; Song Ho Chang; Yasunori Omata; Sakae Tanaka; Takumi Matsumoto (Case Reports in Orthopedics)
Medial bone excrescence at the base of the distal phalanx of the hallux is a common manifestation which is rarely painful. In this case report, we described the first case of the excrescence becoming symptomatic one year after a metatarsophalangeal (MTP) joint arthrodesis of the great toe in a 74-year-old female. The medial bony excrescence which was obscure preoperatively became obvious postoperatively in the anteroposterior foot radiographs. The patient was successfully treated by an excision of the excrescence. In order to clarify the pathology of the excrescence, we reviewed the radiographs with respect to the excrescence before and after hallux surgeries including 97 metatarsal osteotomies and 33 MTP joint arthrodesis. The width of the excrescence measured in the anteroposterior foot radiographs displayed substantial increment one month after the hallux surgeries (osteotomy group: 0.9±0.7 vs. 1.5±0.7 mm, p<0.01; arthrodesis group: 1.3±0.8 vs. 1.8±1.0 mm, p<0.01). However, there was no significant difference in the width of the excrescence between one month after surgery and at the most recent follow-up of around 20 months in average after the surgery (osteotomy group: 1.5±0.7 vs. 1.4±0.7 mm, p=0.62; arthrodesis group: 1.8±1.0 vs. 1.8±0.7 mm, p=0.37). The present case and our radiographic review suggested that the postoperative medial bony excrescence was not the result of change of position of the preexisting excrescence. The correction of pronation deformity through hallux surgeries could emphasize the medial bony excrescence and cause symptomatic irritation upon shoe contact.